Students and staff perception toward psychiatry curriculum in III B.P.T. - DR. SANJIVANI N DHOTE (PT),; DR. MANISHA RATHI (Ph.D),; DR. SUVARNA GANVIR (PT), (International Journal of Pharma and Bio Sciences, 2017)
The course syllabus is a written communication between the course instructor and students, colleagues, and administrators. For this study, we designed a survey to measure faculty and student perceptions of what components of college course syllabi are essential. Need of study to analysis the curriculum of Psychiatry subject in III BPT course.1.Perception of students about Psychiatry curriculum in III B.P.T, 2.Perception of physiotherapy staff about Psychiatry curriculum in III B.P.T. 3. Perception of Psychiatry staff about Psychiatry curriculum in III B.P.T.Physiotherapy.Ethics committee approval was taken to conduct the study. Students & Staff consent was taken to participate in the study. Three types of Questionnaire were prepared to analyse the perception of psychiatry as subject in Physiotherapy UG course. Questionnaire was circulated among the students, physiotherapy staff & psychiatry staff and asked them to mark appropriate answer by using 5 point likert scale. 47 students, 18 PT staff & 10 Psychiatry staff were filled the questionnaire. Data was collected and descriptive analysis was done Concluded from the study that knowledge of Psychiatry subject is very much important as per point of view of students, PT Staff and Psychiatry staff for Physiotherapy Undergraduate course. Although it may not be possible to develop an ideal syllabus that meets the needs and concerns of all stakeholders, faculty members may use the findings of this study to evaluate, and possibly improve, their course syllabus.